Ice road dispatch point -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
Truck dispatch point situated on Old Airport Road, Yellowknife, NT, for the winter ice roads to the Ekati and Diavik diamond mines, and to settlements without permanent road access. Photograph taken March 2012 ...